Fundamentals of Food Microbiology - Jagannathan, S. N. (The Indian Journal of Nutrition and Dietetics, 1968)
This book on food microbiology contains a study of the common microorganisms related to the food science and the growth, and the effects of these organisms on various food products. That includes food poisoning also.